The Politics of Empire and the Architecture of Identity: Public Architecture in New Zealand 1900-1918 - Lochhead, Ian (Architectural History Aotearoa, 2004)
During the period from 1900 to 1918 new governmental buildings were constructed throughout New Zealand as part of a campaign to provide accommodation for government departments. Post offices, court houses and departmental buildings appeared in provincial towns as well as in major cities, almost all products of the government's architectural office, led by John Campbell. The exuberant Imperial Baroque style adopted for these buildings reflects a new national confidence but also follows closely the precedent of British public building of the period. Auckland's former Chief Post Office (1908-11) for example, is closely modelled on Sir Henry Tanner's Central Post Office in London (1907). The extent and consistency of the Government's building programme was intended to promote a sense of national unity although its dependence on British models seems to confirm Hurst Seager's argument that New Zealand had yet to develop a distinctive architectural style. The use of the Imperial Baroque style, culminating in Campbell's design for Parliament Buildings of 1911, reflected New Zealand's strong sense of identification with the British Empire, also expressed through the contributions of its politicians at Imperial Conferences from 1897 to 1911. Unlike their counterparts from Canada and Australia, New Zealand politicians argued for stronger imperial bonds as a way of ensuring greater influence over imperial policies. This paper will argue that in fact, New Zealand public architecture of the period 1900-18 reflects a clear sense of national identity but one that is defined in terms of Britishness and conceived within the larger framework of the security provided by imperial solidarity.